2014
DOI: 10.1007/s13181-014-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Massive Lindane Overdose with Toxicokinetics Analysis

Abstract: Background Lindane is a possible carcinogen with known teratogenicity and immunologic and neurotoxic properties. Despite reports of seizures, coma, and death associated with its use as well as banning of its environmental use by the Environmental Protection Agency (EPA), the US Food and Drug Administration (FDA) still allows treatment with lindane as a second-line scabicide and pediculicide. We present a case of a massive suicidal ingestion of lindane in which the patient survived the ingestion, though he did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There are many different mechanisms, such as blockage of GABAA receptors [4], which could explain the convulsive effect of lindane, but they are not fully understood. On the other hand, it has been proven that H2S mitigates damage to the hippocampus by preventing the loss of GABAB receptors during recurrent febrile seizures [18,19]. In this manner, H2S can achieve a balance between excitation and inhibition during seizures, facilitating the occurrence of hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different mechanisms, such as blockage of GABAA receptors [4], which could explain the convulsive effect of lindane, but they are not fully understood. On the other hand, it has been proven that H2S mitigates damage to the hippocampus by preventing the loss of GABAB receptors during recurrent febrile seizures [18,19]. In this manner, H2S can achieve a balance between excitation and inhibition during seizures, facilitating the occurrence of hyperpolarization.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, PCB administration was associated with cardiac hypertrophy and abnormal blood pressure [ 86 ]. A Clinical report suggested that lindane ingestion (accidental or intentional) was associated with the occurrence of atrial fibrillation and flutter [ 87 ]. A study of the frog atrium suggests that lindane-associated rhythm disorder may reside in the fact that lindane increases rapid delayed outward K + currents which provokes action potential repolarization in the atria [ 88 ].…”
Section: Relation Between Pesticide Exposure and Cardiac Rhythm Disor...mentioning
confidence: 99%